Evaluation of blood supply and metabolism in tumor, axillary lymph node and normal breast tissue with F-18 FDG PET/CT in breast cancer: comparison with pathological prognostic factors - Ummuhan Abdulrezzak; Hulya Akgun; Ahmet Tutus; Mustafa Kula; Serap Dogan; Abdullah Bahadır Oz; Engin Ok (BMC, 2024)
Abstract Background and purpose Perfusion parameters obtained in F-18 FDG PET/CT performed for staging purposes in breast cancers may provide additional information about tumor biology as well as glucose metabolism. The aim of this study was to evaluate throughout F-18 FDG PET/CT the relationship between blood flow and glucose metabolism and histological parameters of the primary tumor, normal mammary gland, and axillary lymph nodes in breast cancer patients. Materials and methods Sixty six female patients (mean age 51 y ± 12,81) were prospectively included to this study. We performed dynamic blood flow (f) study that started with 296-444 MBq (8-12 mCi) F-18 FDG injection and lasted for 10 minutes, and glucose metabolism (m) imaging one hour later. On each frame, mean activity concentration (AC) values (Bq/mL) were recorded on a spherical volume of interest (VOI) having a volume of ~ 1 cm3 on the hottest voxel of primary tumor (T), across normal breast gland (NG) and ipsilaterally axillary lymph nodes (iLN). Correlations among PET parameters and estrogen receptor (ER), progesterone receptor (PR), human epidermal growth factor receptor 2 (c-erbB2) and Ki67 index were analyzed. Results T volume (TV) ranged from 1.1 to 85.28 cm3 [median (IR): 6.44 (11.78)]. There were positive correlations between c-erbB2 and TACf and between c-erbB2 and iLNACf (p = 0.045, r = + 0.248; p = 0.050, r = + 0.242). In the ER positive (ERP) patients, TV and TACm were significantly lower than those of ER negative (ERN) (respectively p = 0.044 and p = 0.041). In patients with two positive Ki-67 indices, iLN-SUVmax was significantly higher than one-positive patients (p = 0.020). There was a negative correlation between NGACm and histological grade of tumor (p = 0.005, r = − 0.365). Conclusions Breast cancer shows differences in progression, metastasis and survival due to its diversity in terms of molecular, biological and angiogenesis. High glucose metabolism in breast cancers is associated with tumor aggressiveness. Being able to examine tumor tissue characteristics such as blood flow and glucose metabolism with a single diagnostic technique and to reveal its relationship with histological parameters can provide a reliable pretherapeutic evaluation in breast cancers.